2010
DOI: 10.1002/mds.23011
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenology of the geste antagoniste in primary blepharospasm and cervical dystonia

Abstract: The geste antagoniste (GA), a relatively common feature of adult-onset primary dystonia, has been systematically evaluated only in cervical dystonia, but it is still unclear whether its frequency and phenomenology differ among the various forms of focal dystonia. We analysed the frequency, phenomenology, effectiveness, and relationship of the GA with demographic/clinical features of dystonia in a representative clinical series of patients with the two most common forms of adult-onset primary dystonia, blepharo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 23 publications
7
70
1
Order By: Relevance
“…This reinforces the idea that the application of a geste antagoniste could exert a modulation of the sensorymotor intergration that is disturbed in dystonia [38][39][40][41]. This effect could be age dependent [17].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This reinforces the idea that the application of a geste antagoniste could exert a modulation of the sensorymotor intergration that is disturbed in dystonia [38][39][40][41]. This effect could be age dependent [17].…”
Section: Discussionsupporting
confidence: 84%
“…It is characterized by its clinical heterogeneity and the possible coexistence of different forms of geste antagoniste in the same patient that allow different degrees of relief [14][15][16][17][18][19]. This gesture can take the form of a classical sensory trick or of a 'forcible' trick [17,20]. A 'forcible trick' consists of performing a forceful counter-pressure in opposition to the dystonic head turn, which may become necessary in more severe forms of dystonia where a purely sensory trick may not be sufficient to counteract the dystonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Diagnosing BSP and assessing the impact of treatments on the condition are major needs in clinical practice and research. Although a new scale specifically developed for rating the severity of BSP has been validated, 5 the diagnosis of BSP is presently based on clinical grounds and is open to bias.…”
Section: Discussionmentioning
confidence: 99%
“…Functioning as a sensory trick, vision may have allowed subjects to better define their head orientation in space and minimize the disruptive effects of dystonia. Although sensory tricks are traditionally associated with cutaneous input by touching the cheek (Deuschl et al,1992;Kaegi et al,2013;Martino et al,2010;Muller et al,2001), recent studies have shown that vision can also act as a sensory…”
Section: Accepted Manuscriptmentioning
confidence: 99%